Caribbean Region : telecommunications sector report : January 2006 (Systec Belgium MaransartBE, 2006)
Examines the Caribbean telecommunications market. Identifies the implementation of key regulatory principles. Provides benchmarks against which regulatory developments and the effects observed in the telecommunications market can be measured.
Keywords: TELECOMMUNICATIONS